Inflation And Exchange Rate On Indonesia Sharia Stock Index (ISSI) 2019-2022 Period - Alfajriyani, Siti; Musthofa, Muhammad Wakhid (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This research was conducted with the aim of finding out how much influence inflation and the exchange rate have on Indonesia sharia stock index (ISSI) for the 2019-2022 period. This research is quantitative research with the type of data used is secondary data of the time series data type . The method used is the multiple linear regression method with data processing using the Eviews12 program. The data taken is data from each variable from the beginning of 2019 to the end of 2022, based on quarters 1, 2, 3 and 4 with a sample of 16 data. In this research, the author carried out two tests, namely the classical assumption test as a condition for fulfilling the assumptions of the OLS method and hypothesis testing to analyze the influence of inflation and exchange rates on ISSI. The conclusion of this research is that inflation has a significant positive effect and the exchange rate has a significant negative effect.